2019
DOI: 10.1111/1755-0998.13009
|View full text |Cite
|
Sign up to set email alerts
|

Index hopping on the Illumina HiseqX platform and its consequences for ancient DNA studies

Abstract: The high‐throughput capacities of the Illumina sequencing platforms and the possibility to label samples individually have encouraged wide use of sample multiplexing. However, this practice results in read misassignment (usually <1%) across samples sequenced on the same lane. Alarmingly high rates of read misassignment of up to 10% were reported for lllumina sequencing machines with exclusion amplification chemistry. This may make use of these platforms prohibitive, particularly in studies that rely on low‐qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 54 publications
1
99
0
Order By: Relevance
“…In summary, the global data set of genomes analysed here contributes further to the emerging consensus (Árnason, Lammers, Kumar, Nilsson, & Janke, 2018;Arnold, 2016;Gopalakrishnan et al, 2018;Malinsky et al, 2018;Sinding et al, 2018;Tusso et al, 2018) that the relationship among natural populations is rarely well represented as a bifurcating tree. The evolutionary history of natural populations can include episodic long-range dispersal, population replacement and admixture which greatly transform the distribution of global genetic variation.…”
Section: Discussionmentioning
confidence: 65%
“…In summary, the global data set of genomes analysed here contributes further to the emerging consensus (Árnason, Lammers, Kumar, Nilsson, & Janke, 2018;Arnold, 2016;Gopalakrishnan et al, 2018;Malinsky et al, 2018;Sinding et al, 2018;Tusso et al, 2018) that the relationship among natural populations is rarely well represented as a bifurcating tree. The evolutionary history of natural populations can include episodic long-range dispersal, population replacement and admixture which greatly transform the distribution of global genetic variation.…”
Section: Discussionmentioning
confidence: 65%
“…Nonetheless, we observed that many spurious taxa most likely originate from samples multiplexed with the de ned communities in one sequencing run, despite the implementation of multiple negative controls and an automated sample processing work ow. One cause for spurious sequences, termed index-hopping, was previously identi ed to account for 0.47% of reads, with samples with the fewest reads being affected the most [36]. As de ned in the present study by using de ned communities as references, spurious taxa do not necessarily represent true artifacts (i.e.…”
Section: Discussionmentioning
confidence: 64%
“…Specifically, for all loci at all AT samples, more than 90% of read pairs had the AT allele, and for all loci at all A. coluzzii samples, more than 90% of read pairs had the A. coluzzii allele. The small numbers of incorrect reads could be due to index hopping among these jointly-sequenced samples (van der Valk, Vezzi, Ormestad, Dalén, & Guschanski, 2019) or low-level contamination. Coverage at the negative control was lower but non-negligible (76 to 1460 read pairs per locus, mean = 411.6), presumably due to similar errors.…”
Section: Resultsmentioning
confidence: 99%